Peningkatan Hasil Belajar Siswa dalam Pembelajaran PKn dengan Menggunakan Model Kooperatif Tipe TPS di Sekolah Dasar - Addha, Wulandari; Reinita, Reinita; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this research is cleary describe an improvement of PKN learning result by using cooperative model of TPS type 4th class SDN 52 Kuranji, Padang. This reasearch use a qualitative and quantitative approaches with an action classroom method (PTK). The subjects of a research are a teacher and 20 students. A research result by cycle planning I is about 78,57% then rises by cycle II about 92,85%. An  from teacher side cycle I is about 78,12% and cycle II rises about 90,62%. In addition, from student aspect cycle I is about 76,56% and rises by cycle II about  87,50%. Then the student learning result from cycle I about 76,10 and rises by cycle II 86,08.  Keywords: Civics, cooperative model of TPS type